Strategi Bimbingan dan Pengawasan Bagi Narapidana Asimilasi di Rumah Dalam Upaya Mengurangi Dampak Pandemi Covid-19 - Sri Marhani (UIN Siber Syekh Nurjati Cirebon, 2021)
The spread of Coronavirus Disease 2019 (Covid-19) affects the life of the world community. In Indonesia, the formation of the Task Force for the Acceleration of Handling Coronavirus Disease 2019 (Covid-19) refers to Presidential Decree Number 7 of 2020, dated March 13, 2020. This study aims to determine the pattern of guidance and supervision in undergoing the assimilation process at home during the Covid-19 pandemic and to analyze the obstacles faced when implementing the pattern of mentoring and supervision, as well as what strategies need to be developed to overcome these obstacles. The research method used is a qualitative research method while the data analysis uses qualitative data analysis, which includes data reduction, data display, and conclusions. The results of the study indicate that the process of mentoring and supervision that undergoes assimilation at home and integration is in accordance with the implementation of the guidance stipulated in Government Regulation Number 31 of 1999 and has applied and applied the knowledge of the social work profession. Includes Engagement, Intake, Contract, Assessment, Planning, Intervention and Evaluation.